SYNTHESIS OF OXAZOLO [3, 2-b] 1, 2, 4- TRIAZINES A NOVEL HETEROCYCLIC SYSTEM (Journal of Sciences, Islamic Republic of Iran)
The synthesis of 6- methyl- 2- phenyl- 7H- oxazolo [3,2-b] 1,2,4-Triazine- 7-one (6, R=Ph) and its 2-P- bromophenyl analogue to the two members of a new heterocyclic system is described